Structural Design and Obstacle-surmounting Performance Research of Wheel-track Hybrid Robots - Zhao Jiahui; Chen Minghui; Liang Zhiyuan; Li Qingdu (Jixie chuandong)
In order to stably exert the best obstacle-surmounting performance of the wheel-track compound robot, a new wheel-track compound robot that can switch multiple motion modes according to the environment is developed. The robot can switch between the upright motion and the crawler motion mode, and the position of the center of gravity of the robot can be greatly adjusted by the rotation of the swing arm, which has better obstacle-surmounting performance. On the basis of gait planning and motion mechanism analysis of the robot, kinematics and dynamics analysis of the typical step crossing motion process are carried out, which verifies the feasibility of the robot mode switching, and calculates the maximum theoretical value of the step height that the robot can climb. Finally, using the simulation software, according to the theoretical values obtained by the calculation, the simulation test of the robot's step climbing process is carried out. The results verify the accuracy of the calculated values and the obstacle-surmounting performance of the robot.